RELIEF MURAL IN SANTINIKETAN: RAMKINKAR BAIJ’S SCULPTURAL LANGUAGE - Biswas, Pradipta; Singh, Udaya Narayana (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Ramkinkar Baij is recognised as a pioneering artist in the history of Indian sculpture and is often referred to as the father of modern Indian sculpture. He introduced a new visual language and technique that closely correspond to the concepts and nature of his works, adopting dynamic forms and expressive textures that convey emotion and movement. The construction, force, rhythm, and inner vitality apparent in his work distinguish him from other sculptors. His sculptures frequently focus on the lives of marginalised individuals, highlighting their struggles and fortitude in society. Baij developed a revolutionary throwing process and employed new media to merge his sculptures with the local textures, people, and landscapes within their environments, enabling an enhanced connection between the artwork and the community it represents. His renowned open-air environmental works, such as Mill Call, Santhal Family, Thresher, and Sujata, have introduced a unique dimension to Indian modern sculpture. His expertise in mural art is on par with the significance of his well-documented open-air sculptures and drawings. His work to relief murals in Santiniketan has considerably augmented the history of mural art during the modern Indian art era. In addition to his sculptural achievements, Baij has made a durable impact on relief mural art. This study considers the concepts, visual language, and techniques used in his mural art. It also emphasises his contributions to society and how his mural journey has motivated future generations of artists. Furthermore, the study considers how the media he pioneered have gained widespread popularity and keep influencing the artistic language of contemporary society.